Study of haematological parameters in malaria: a prospective study - Manjula J Babariya; Jitendra kumar S. Parmar (Tropical Journal of Pathology and Microbiology, 2020)
Background: A blood parasites plasmodia is responsible for malaria hence there are haematological alterations in malaria. The haematological changes that have been reported to accompany malaria include anaemia, thrombocytopenia, leucocytosis and leucopenia.Methods: Total 585 smear positive malaria cases were taken and various haematological parameters were studied.Results: Out of 585 smear positive cases, P. vivax was positive in 422 (72%) cases, while P. falciparum was positive in 160 (27%) cases and mixed infection was found in 3 (1%) cases. Anaemia was seen in 420 (71.79%) cases. Normocytic normochromic blood picture was the most common type in anaemic patients 223 (38.11%). Next common finding was Normocytic hypochromic RBCs 185 (31.62%). Microcytic hypochromic RBCs found in 152 (25.98%) cases. Thrombocytopenia was seen in total 490 (83.76%) of the patients. Moderate thrombocytopenia was more common and present in 409 (70%) of patients while Severe thrombocytopenia was seen in 81 (13.84%) of cases. In falciparum malaria thrombocytopenia was present in 90% of the patients while it was present in 81.27% of the patients in vivax malaria. 129 cases (22.05%) shows leucopoenia out of which 81 (13.84%) belong to P. vivax, 45 (7.69%) belong to P. falciparum and 3 (1%) were belong to mixed infection. Total Leucocyte Count was normal in 77.95 % of the patients.Conclusions: Various haematological findings can help in early diagnosis of malaria which is essential for timely and appropriate treatment which can limit the morbidity and prevent further complications.